RANCANG BANGUN SISTEM PERHITUNGAN PENILAIAN AKREDITASI SEKOLAH/MADRASAH BERBASIS WEB - Fikriyyah; Putra Eka Prismana, I.G.L. (Inovate, 2016)
The calculation of the value of accreditation is done by assessors using Microsoft Excel, copy paste method is usedto include the value of National Education Standards (NES) / Standar Nasional Pendidikan which stands for eightstandards. It can cause data easily changed by irresponsible person which make invalid data.On the other hand thevalue of accreditation is important to mark the establishment of competence to educational organizations. To solve this problem, calculation system of accreditation assessment for elementary or level education is designwith web technology. It is implement with the latest Laravel technology which use PHP for programminglanguage. For database system, MySQL is choose to handle data. Standard of calculation use regulation for scoringand ranking which legalized by Minister of Education in Indonesia by the Number 11/2009. The design system ismade based on SOP for accreditation of elementary education in Indonesia.As result, web based application is made. It can calculate the value which entered by the accessor and send it rightaway to the server. Several level of user is configure to maintain and administer the entry is specific to level ofuser. It can also give report to concern user as per table, graphic, and print it out to PDF. Many things not to bedone right how such as warning system is detailed by month, use access for school/institution, upload by excelsystem. Hopefully this minor can be accomplish by next research. Keywords : Accreditation School, Elementary School, Laravel, Calculation System